Biochemical performance of native and introduced clam species living in sympatry: The role of elements accumulation and partitioning - Velez, Cátia (2022)
The present study reports metal and arsenic contamination in sediments, as well as element accumulation and partitioning in native (Ruditapes decussatus and Venerupis corrugata) and introduced (Ruditapes philippinarum) clam species living in sympatry at the Obidos lagoon (Portugal). The biochemical performance and the human health risks derived from the consumption of these species are also discussed. The results obtained showed that R. decussatus was the most abundant species in all the sampling sites, revealing that the introduced clam has not yet supplanted the native species. The concentration of elements was higher in areas with higher Total Organic Matter (TOM) and fines content, being Chromium (Cr), Copper (Cu) and Lead (Pb) the most abundant metals. Clams from these areas showed the highest concentration of elements but the lowest bioaccumulation levels. Furthermore, except for As, higher concentration of elements was found in clams insoluble fraction, the less toxic fraction to the organisms. Due to the low contamination levels and because elements, except As, were mainly allocated to the insoluble fraction, clams presented similar biochemical parameters among distinct areas, with no significant oxidative stress induced. Furthermore, clams from the Obidos lagoon represent a low health risk to human consumption since, except for As, their contamination levels were below the maximum permissible limits defined by international organizations.